Terrorism : Malaysia cooperation with asean post 9/11 - Ronnie, Ranjit Singh (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The attacks of 9/11 have marked a significant event not only to the US but to the rest of the world. The attacks have direct impact to the world in terms of downfall of economy, security, and destruction of human lives and properties. It has portrayed of the danger on the act of terror and its capability to produce such effects. Southeast Asian region again, is not free from this threat. Terrorist organizations such as Jemaah Islamiyah (JI), Abu Sayyaf Group (ASG), Darul Islam (DI), and Kumpulan Mujahideen Malaysia (KMM) are found operating in the region including Malaysia. Moreover, there are also large scale bombings that occurred due to terrorists activities such as bombings in Indonesia and the Philippines. Given the fact that terrorism is a transnational crime today, it is impossible for a country to act alone in handling this threat and Malaysia is not an exception. The aim of this thesis is to discuss on the need for Malaysia to cooperate with ASEAN in counter-terrorism. Apart from that, this thesis also focuses on the initiatives involved by Malaysia in engaging ASEAN in countering terrorism in the post 9/11 era. The final aim of this thesis is to evaluate the importance of Malaysia to cooperate with ASEAN in countering terrorism. Neo-Realism, Pluralism and Regionalism theory is best applicable to the context of this research due to the function of ASEAN in countering terrorism apart of the focus of areas including social and economic aspects. The review of ASEAN declarations, conventions, agreements, and meeting statements and interview is used as methods for data collection.